Alpha2beta1 Integrin Polymorphism in Diffuse Astrocytoma Patients - Teixeira, Silvia A.; Burim, Regislaine V.; Viapiano, Mariano S.; Bidinotto, Lucas T. [UNESP]; Nagashi Marie, Suely K.; Fleury Malheiros, Suzana M.; Oba-Shinjo, Sueli M.; Andrade, Augusto F.; Carlotti, Carlos G. (Frontiers, 2022)
Integrins are heterodimeric transmembrane glycoproteins resulting from the non-covalent association of an α and β chain. The major integrin receptor for collagen/laminin, α2β1 is expressed on a wide variety of cell types and plays an essential role in the adhesion of normal and tumor cells to the extracellular matrix. Integrin-triggered signaling pathways promote the invasion and survival of glioma cells by modifying the brain microenvironment. In this study, we investigated the association of a specific genetic polymorphism of integrin α2β1 with the incidence of diffusely infiltrating astrocytoma and the progression of these tumors. Single-nucleotide polymorphism in intron 7 of the integrin ITGA2 gene was examined in 158 patients and 162 controls using polymerase chain reaction and restriction enzyme analysis. The ITGA2 genotype +/+ (with a BglII restriction site in both alleles) exhibited higher frequency in grade II astrocytoma compared to control (P = 0.02) whereas the genotype -/- (lacking the BglII site) correlated with the poorest survival rate (P = 0.04). In addition, in silico analyses of ITGA2 expression from low-grade gliomas (LGG, n = 515) and glioblastomas (GBM, n = 159) indicated that the higher expression of ITGA2 in LGG was associated with poor overall survival (P < 0.0001). However, the distribution of integrin ITGA2 BglII genotypes (+/+, +/-, -/-) was not significantly different between astrocytoma subgroups III and IV (P = 0.65, 0.24 and 0.33; 0.29, 0.48, 0.25, respectively) compared to control. These results suggest a narrow association between the presence of this SNP and indicate that further studies with larger samples are warranted to analyze the relation between tumor grade and overall survival, highlighting the importance of determining these polymorphisms for prognosis of astrocytomas.
Keywords: brain microenvironment; extracellular matrix; invasion; ITGA2; low grade glioma; single nucleotide polymorphism; tumor progression